Kesesuaian Porsi Lauk Daging Ayam Yang Diterima Pada Makanan Biasa - Rani Putri; Reni Sofiyatin; Lalu Khairul Abdi; AASP Chandradewi (Poltekkes Kemenkes Mataram, 2019)
Large portions are often one thing when serving food, especially in food serving. It is still an advantage and lack of portion because there is no right size in food processing. food consumption must be in accordance with the standard portion determined by the hospital nutrition installation. large portions will affect the nutrients contained in a food. This study aims to determine the suitability of standard portions of side dishes of chicken meat received in ordinary food at Sanjiwani Hospital Gianyar Regency. This study was a descriptive observational study with a crossectional approach. This research was conducted for 3 days in April 2019 at Sanjiwani Hospital Gianyar Regency. The number of samples is 30 servings. The proportion of portions served is measured by the food weighing method for 3 days. The results showed that the standard suitability of the portion of chicken received at Sanjiwani General Hospital in Gianyar Regency was largely incompatible, namely 83.3%, while those in accordance with the standard portion were 16.6%.